Dissection of 16S rRNA Methyltransferase (KsgA) Function in Escherichia coli - Inoue, Koichi (American Society for Microbiology (ASM), 2007)
A 16S rRNA methyltransferase, KsgA, identified originally in Escherichia coli is highly conserved in all living cells, from bacteria to humans. KsgA orthologs in eukaryotes possess functions in addition to their rRNA methyltransferase activity. E. coli Era is an essential GTP-binding protein. We recently observed that KsgA functions as a multicopy suppressor for the cold-sensitive cell growth of an era mutant [Era(E200K)] strain (Q. Lu and M. Inouye, J. Bacteriol. 180:5243-5246, 1998). Here we observed that although KsgA(E43A), KsgA(G47A), and KsgA(E66A) mutations located in the S-adenosylmethionine-binding motifs severely reduced its methyltransferase activity, these mutations retained the ability to suppress the growth defect of the Era(E200K) strain at a low temperature. On the other hand, a KsgA(R248A) mutation at the C-terminal domain that does not affect the methyltransferase activity failed to suppress the growth defect. Surprisingly, E. coli cells overexpressing wild-type KsgA, but not KsgA(R248A), were found to be highly sensitive to acetate even at neutral pH. Such growth inhibition also was observed in the presence of other weak organic acids, such as propionate and benzoate. These chemicals are known to be highly toxic at acidic pH by lowering the intracellular pH. We found that KsgA-induced cells had increased sensitivity to extreme acid conditions (pH 3.0) compared to that of noninduced cells. These results suggest that E. coli KsgA, in addition to its methyltransferase activity, has another unidentified function that plays a role in the suppression of the cold-sensitive phenotype of the Era(E200K) strain and that the additional function may be involved in the acid shock response. We discuss a possible mechanism of the KsgA-induced acid-sensitive phenotype.